A Review of Magnesium Alloys In Vivo Antibacterial Properties: Challenges, Solutions, and Perspectives in Implant-Associated Orthopedic Infections - Khlusov I. A. Igor Albertovich; Prosolov K. A. Konstantin Alexandrovich; Sharkeev Yu. P. Yury Petrovich; Gorokhova A. V. Anna Viktorovna; Volinsky A. A. (2025, 2025)
Title screen